2016
DOI: 10.5455/bcp.20150703013708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Symptom Ratings and Other Clinical Features on Short-Term Treatment Response to OROS Methylphenidate in Children and Adolescents with ADHD in a Naturalistic Clinical Setting

Abstract: Objective To investigate the effect of Attention Deficit Hyperactivity Disorder (ADHD), antisocial behavior and anxiety/depression ratings of mothers, and child and adolescents’ age, gender, ADHD subtype, and comorbidity on one-month drug treatment response to OROS methylphenidate in ADHD in a naturalistic setting. Methods The analyses included 223 subjects (191 boys, 32 girls; age 6–15 years, mean: 9.4) treated with OROS methylphenidate (18–72 mg/day, mean: 31 mg/d; 0.4–1.4 mg/kg/d) for one-month. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Because, several prior studies suggested that baseline rating scores were important predictors of treatment response. This might be due to regression to the mean effect and implies that subjects with highest baseline scores have a higher chance of reduced post-treatment scores [30,31]. Baseline scores were higher in medikinet group and it may *% refers to percentage of subjects in whom the side effect was rated 1 or higher on the scale of the severity (1-9); %severe refers to the percentage of subjects in whom the side effect was rated 7 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Because, several prior studies suggested that baseline rating scores were important predictors of treatment response. This might be due to regression to the mean effect and implies that subjects with highest baseline scores have a higher chance of reduced post-treatment scores [30,31]. Baseline scores were higher in medikinet group and it may *% refers to percentage of subjects in whom the side effect was rated 1 or higher on the scale of the severity (1-9); %severe refers to the percentage of subjects in whom the side effect was rated 7 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…It was simply based on the mother’s overall impression of her child’s behavior. The accuracy of such global impressions has been proven to be effective in other studies [ 16 ]. Watching TV, which was most prevalent (154/190, 81.0%) in our sample, was previously noted by other investigators who found no association between watching TV and emotional symptoms, hyperactivity, inattention, or peer relationship problems [ 17 ].…”
Section: Discussionmentioning
confidence: 99%